Atmospheric plasma oxidative polymerization of ethylene dioxythiophene (EDOT) for the large‐scale preparation of highly transparent conducting thin films. Issue 4 (16th November 2017) - Abessolo Ondo, Dominique; Loyer, François; Chemin, Jean‐Baptiste; Bulou, Simon; Choquet, Patrick; Boscher, Nicolas D.
Abstract : A simple and easily scalable approach toward the simultaneous synthesis and deposition of conducting plasma‐polymerized 3, 4‐ethylenedioxythiophene (ppEDOT) coatings is reported. Our atmospheric‐pressure dielectric barrier discharge (AP‐DBD) approach, operating at room‐temperature and atmospheric‐pressure, does not involve the use of oxidants other than the reactive oxygen species (ROS) formed by the open air Ar/O2 dielectric barrier discharge. The oxidative polymerization of EDOT is confirmed using UV‐visible (UV‐vis), Raman, and Fourier‐transform infrared (FTIR) spectroscopy. High‐resolution mass spectrometry (HRMS) investigations highlight the discrepancies between the synthesized ppEDOT and conventional PEDOT. Finally, highly transparent (i.e., 98% transmittance) and durable conducting thin films are deposited on polyethylene naphthalate (PEN) foils. Abstract : The chemical vapor deposition (CVD) polymerization of ethylene dioxythiophene using a nanosecond pulsed atmospheric plasma is demonstrated to provide an easily up‐scalable one‐step method toward the deposition of durable, highly transparent, and conductive organic layers. An extensive mass‐spectrometry study highlights the formation of poly(thiophene‐co‐EDOT) chains and illustrate the benefits and limitations of the proposed plasma‐based approach.